Juridical Provisions on Government Policies Towards Marginal Economic Actors in Indonesia in the Perspective of Islamic Law - Alidar, EMK; Maulana, Muhammad; Syah, Yuhasnibar; Usman, Bustamam (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This study investigates the legal provisions for dealing with street vendors in Banda Aceh and Yogyakarta, utilizing the Qanun no. 3/2007 and the Mayor Regulation no. 26/2002, respectively. It investigates the variables that constitute the basis for the creation of policies for dealing with street sellers and evaluates policy formulations for dealing with street vendors in the two provincial capitals in a more accommodating and comprehensive manner. This is a normative legal research that examines legal data in the form of the rule of law by evaluating statutes and Islamic law. The results indicated that the Qanun for the City of Banda Aceh and the Perwal Yogyakarta were legally designed to govern and control street vendors in compliance with the urban planning and aesthetics of the city. However, the Banda Aceh Qanun addressing street vendors must be tied to the Mayor's Regulation 44 of 2016 about the role and function of Wilayatul Hisbah (WH) and Satpol PP (Civil Police), which reflect Islamic shari'a standards. Although the Mayor of Yogyakarta Regulation No. 26/2002 on street vendors has been designated as a source and tourist attraction that must be managed responsibly, this has a positive impact on street vendors. The regulation has included cultural issues with such care that it has a favorable effect on their economic earnings. Although other aspects, such as the issuance of business licenses, impartial spatial layouts, and coercive measures against street vendors, still need to be developed. Nevertheless, the Banda Aceh government's comprehensive WH policy integrates Islamic law and the Yogyakarta Perwal, which accommodates local and cultural values in accordance with the rule of law that governs and disciplines the society.